Effect of Contact Time of Rice Husk Ash and Poly Aluminum Chloride to Reduce the Concentration of Rhodamin B Dyes Using the Adsorption-Fluidization Method - Agung Sugiharto; Imam Hoyali; Ahmad Fadli Arya Ghifari; Tasya Hudani Nabilla (CHEMICA: Jurnal Teknik Kimia, 2020)
The disposal of rhodamine B of industrial wastewater into the environment without treatment causing water pollution. The purpose of this study is to utilize rice husks as activated carbon which is used to treat industrial wastewater through the adsorption – fluidization process. Also, to determine the effect of variations in contact time on the adsorption process. Carbon from rice husk is activated used 36% HCl. The adsorption process used activated carbon is variated in contact time for 0, 30, 60, 90, 120, and 150 minutes. Based on the result of this research, the optimal contact time is 120 minutes. At that time, activated carbon from rice husk can reduce initial levels of 50 ppm to 1.142 ppm.